Does one always have to initiate a judicial or administrative proceedings after obtaining information of possibility of committing crime to execute a penalty sanction? - JAKUBIAK, TOMASZ (Prawo Kanoniczne, 2017)
The intention of the legislator is to apply penalties in the Church as rarely as possible. Before instigating the punishment for the criminal, one should use all other means of pastoral or legal nature. This is because the entire activity of the Church should be subordinated to the highest principle stated in the final canon of the Canon Law. According to it, the salvation of souls must always be the supreme law in the Church (can. 1755 CIC). The ordinary, who is responsible for the discipline in the community entrusted to him, must advocate for the rights of the canon law theologically, not only formally. Even the decision on the initiation of the criminal proceedings on the criminal or administrative way, is to help the accused to enter the path of salvation. Due to prescription a criminal action, in many cases the application of penalty is impossible.